Undergraduate medical education; how far should we go? - Hani TS Benamer (Libyan Journal of Medicine, 2007)
Medical education is a leading step in improving the quality of health services all over the world; in recent years such an important issue has changed tremendously. New concepts and theories were introduced particularly in undergraduate medical education, these may include beyond curriculum education and the concept of problem based learning (PBL). The latter was introduced by Barrows at McMaster University, Canada over three decades ago and will gain the main emphasis in this article. PBL has shown to be valuable and reflects major improvements in undergraduate medical education. Incorporation of such changes will rarely bear priority in developing countries such as Libya, where the debate about the challenges of undergraduate medical education and the importance of the problem-based learning has just started. However, every one who is involved in medical education has his own views about the process of teaching and that tends to reflect on the way he teaches.Here are my personal views about undergraduate medical education which will be discussed by answering three main questions: 1) How did I develop my views? 2) What are my views? 3) How these views affect the way I teach?